JÖRG RÜPKE, PANTHEON. A NEW HISTORY OF ROMAN RELIGION. PRINCETON, PRINCETON UNIVERSITY PRESS, 2018 - Csaba SZABÓ (Journal of Ancient History and Archaeology)
Jörg Rüpke, Pantheon. A new history of Roman religion. Princeton, Princeton University Press, 2018, 551 p. 64 photos, ISBN 9780691156835.